4CPS-230 Antiarrhythmic therapy evaluation in a hospital setting. (14th March 2021) - Zavaleta, E; Chaverri, JM; Diaz, JP; Serrano, B; Kang, GY
Abstract : Background and importance: Within the hospital setting, arrhythmias prolong hospitalisations, worsen the patient's clinical status and can increase the mortality rate. It is often difficult to choose between the available antiarrhythmic therapies. Currently in our facilities, there are no antiarrhythmic or subsequent anticoagulation drug selection protocols. Aim and objectives: The aim of the study was to characterise admitted patients that had inhospital arrythmias and analyse their antiarrhythmic therapy, anticoagulation needs and drug interactions to evaluate the appropriate use of these drugs according to international guidelines and help to establish evidence based pharmacotherapeutic guidelines. Material and methods: A retrospective observational study of hospitalised patients over a 2 year period was conducted. Information was obtained from the hospital's inpatient management systems, and IBM SPSS software was used for data processing. Results: In this study, 270 patients were analysed, most in the 70-year-old age group, with a prolonged hospital stay. In cases of atrial fibrillation, it was found that some loading doses were omitted, or the oral route was used when amiodarone administration was required. In 51% of patients, arrhythmia was stabilised in the outpatient setting; in the remaining 39%, arrhythmia was stabilised during hospitalisation without requiring in-home medication. As shown in figure 1, most of these patients received optimal antiarrhythmic therapy. When evaluating the need for anticoagulation in patients who had atrial fibrillation based only on the CHA2DS2-VASc score, only 18.5% received optimal treatment. Among the studied population, more than 300 drug interactions were found and related to QTc prolongation that needed to be monitored. Conclusion and relevance: Antiarrhythmic prescription was adequate in most cases. Amiodarone was the most prescribed antiarrhythmic and presented multiple drug interactions. In the studied population, the anticoagulant selection was not optimal based on the evaluation of CHA2DS2VASc2. It is necessary to improve anticoagulation therapy in patients with arrythmias. There is room for improvement, and the clinical pharmacist could collaborate in optimisation, improving the final results, and avoiding complications and drug related adverse effects. Creating a drug dispensing protocol in addition to a comprehensive clinical evaluation for antiarrhythmic therapy, taking all the risk factors, drug interactions and each patient's particular needs into consideration, is essential. References and/or acknowledgements: None Conflict of interest: No conflict of interest